2011
DOI: 10.1074/jbc.m111.283648
|View full text |Cite
|
Sign up to set email alerts
|

O2 Reactions at the Six-iron Active Site (H-cluster) in [FeFe]-Hydrogenase

Abstract: [FeFe]-hydrogenase (H 2 ase) 4 proteins are the most active biological catalysts for the production of molecular hydrogen (H 2 ) from proton reduction, with reported turnover rates of up to 10 4 s Ϫ1 (1, 2). Therefore, these enzymes are of high interest for biotechnology, aiming at the generation of H 2 as a renewable fuel (1, 3-5). However, a severe limitation for such applications is the rapid inactivation of [FeFe]-H 2 ases by dioxygen (O 2 ) (6, 7). Understanding the mechanism of O 2 -induced inactivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
144
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 85 publications
(152 citation statements)
references
References 79 publications
7
144
0
1
Order By: Relevance
“…However, configurations with (semi) bridging or equatorial H-species were considered as well (12,14,36) and may result from structural flexibility of the H-cluster (36). Such structural dynamics may facilitate apical or equatorial ligand binding at the distal iron ion and may also be relevant for O 2 inactivation of the enzymes via reactive oxygen species formation (24,29,30,60,61). Our protocol for selective preparation of H ox with eight distinct isotopic labeling patterns introduces spectroscopic probes at individual positions at the cofactor.…”
Section: Discussionmentioning
confidence: 99%
“…However, configurations with (semi) bridging or equatorial H-species were considered as well (12,14,36) and may result from structural flexibility of the H-cluster (36). Such structural dynamics may facilitate apical or equatorial ligand binding at the distal iron ion and may also be relevant for O 2 inactivation of the enzymes via reactive oxygen species formation (24,29,30,60,61). Our protocol for selective preparation of H ox with eight distinct isotopic labeling patterns introduces spectroscopic probes at individual positions at the cofactor.…”
Section: Discussionmentioning
confidence: 99%
“…According to X-ray absorption measurements, exposing the enzyme from Cr to O 2 damages the 4Fe4S subcluster; this suggested that O 2 binding to Fe d results in the formation of a reactive oxygen species (ROS) that diffuses towards the 4Fe4S subcluster and destroys it. 16,18 According to the DFT studies of Reiher 19,20 and Pachter, 21 this ROS could be the OOH radical or H 2 O 2 . However, this mechanism conflicts with a recent report according to which the O 2 -damaged enzyme from Cr harbors an intact 4Fe4S subsite and no 2Fe subcluster, and the observation that the O 2 -damaged enzyme is repaired upon insertion of a synthetic analogue of the 2Fe subcluster.…”
Section: Introductionmentioning
confidence: 99%
“…As a response to anaerobiosis the unicellular green alga Chlamydomonas reinhardtii develops a complex fermentative metabolism (Gfeller and Gibbs, 1984;Hemschemeier and Happe, 2005;Mus et al, 2007;Hemschemeier et al, 2008b;Philipps et al, 2011) with molecular hydrogen (H 2 ) as one key metabolite. Hydrogen is produced by an oxygen-sensitive [FeFe]-hydrogenase (Stripp and Happe, 2009;Lambertz et al, 2011) that is linked to the photosynthetic electron transport chain via ferredoxin PETF (Winkler et al, 2009). Chlamydomonas expresses two hydrogenaseencoding genes, [FeFe]-hydrogenase isoform1 (HYDA1) and HYDA2 (Forestier et al, 2003), but the HYDA1 protein seems to be the primarily active hydrogenase isoform in the green alga (Godman et al, 2010;Meuser et al, 2012).…”
mentioning
confidence: 99%